The original number is 3.
I actually began with the guess-and-check method, but seeing as that won't always work, let's go over the formal way. To get the original number, you first need to determine how many times the number was squared.
To make it simple, let's use x to focus on the exponents. The number was squared 3 times, so x^2, x^2, x^2. Basically, you need to multiply. 2 * 2 * 2 = 8. So, now find the 8th root of 6561 (depending on the calculator, you can just input it). You should come up with 3. Let me know if this part confuses you.
To find the next 2 numbers, you just need to continue the pattern.
6561^2 = 43,046,721
43,046,721^2 = 1,853,020,188,851,841
To my knowledge, which means this could be wrong, they're both perfect squares. Since the number to get them both were whole numbers, they should both have a square root that equals a whole number.
Original number (3): Not a perfect square (3 is not the square of any integer). First intermediate number (9): A perfect square (9 is the square of 3). Final number (6561): A perfect square (6561 is the square of 81). So, the only perfect square in the sequence is the first intermediate number, 9.
Here's why:
Original number: Starting with an unknown number, let's call it x. Squaring it gives us x^2.
First intermediate number: Squaring x^2 again, we get (x^2)^2 = x^4.
Final number: Finally, squaring x^4 one last time, we reach the given number, 6561: (x^4)^2 = x^8 = 6561.
Now, let's backtrack to find the original number x:
Since 6561 is the square of 81, and 81 is the square of 9, we can conclude that the original number x must be the square root of 9, which is 3.
Therefore, the sequence of numbers you provided is indeed correct:
Original number: 3 (squared to get 9)
First intermediate number: 9 (squared to get 81)
Final number: 81 (squared to get 6561)
Let g be the function given by g(x)=-3x^2-2x+3 evaluate g(-2)
g(x) = -3x² - 2x + 3
g(-2) = -3(-2)² - 2(-2) + 3
g(-2) = -12 + 4 + 3 = -5
in a triangle, if the second angle is 2 times the first angle and the third angle is 3 times the first angle,find the angles of the triangle.
a + b + c = 180
b = 2a
c = 3a
a + 2a + 3a = 180
6a = 180
a = 30
b = 2(30)
b = 60
c = 3(30)
c = 90
Answer:
a = 30
b = 60
c = 90
4 1/5 divided by 2/3 express your answer as a mixed number in Simplest form
4 (1/5 ) = 21/5
21 / 5 divided by 2 / 3 equals
21 / 5 * 3 / 2 equals 63 / 10 equals
6 (3 / 10)
A coffee bean processor can dry 4,815 pounds of coffee beans in 3 hours. Which unit rate correctly reflects the speed of the processor?
A. 1,926 pounds/hour
B. 2,408 pounds/hour
C. 10.13 pounds/minute
D. 26.75 pounds/minute
Answer:
D. 26.75 pounds/minute
Step-by-step explanation:
For calculate unit rate that reflects the speed of the processor we can use the following equation:
[tex]Speed = \frac{Total Pounds}{RequiredTime}[/tex]
Taking into account that the answers are in pounds per hour and pounds per minute, we re going to calculate the speeds in booth units.
1. Speed in Pounds per hours: Replacing Total Pounds by 4,815 and Required time by 3 hours, we get:
[tex]Speed = \frac{4,815Pounds}{3 Hours}=1,605 Pounds/hour[/tex]
2. Speed in Pounds per minute: Every hour have 60 minutes, the 3 hours have 180 minutes, so replacing Total Pounds by 4,815 and Required time by 180 minutes, we get:
[tex]Speed = \frac{4,815Pounds}{180 Hours}=26.75 Pounds/hour[/tex]
So, chosen the rate that appear in the answers, we can say that the correct answer is D. 26.75 pounds/hours.
HELP!!!! An electrician cuts a 26 ft piece of wire into two pieces. One piece is two feet longer than the other. How long are the pieces?
Let 1 piece = X
The 2nd piece would be X + 2 feet
Add:
x +x+2 = 26 feet
2x +2 = 26 feet
Subtract 2 from each side:
2x = 24
Divide both sides by 2:
x = 24 / 2
X = 12
One piece is 12 feet the other piece is 14 feet.
a number d minus 2 is less than -1 ?
d - 2 < -1 is how this inequality would be displayed.
However, we can solve for the value of d by treating this like a standard algebraic equation.
d - 2 < -1
Add 2 to both sides.
d < 1
The value of d is less than 1.
Let me know if you have any other questions.
Answer:
Given phrase,
a number d minus 2 is less than -1
∵ '-' is the sign of minus,
⇒ d minus 2 = d - 2
Also, '<' is the sign of less than,
⇒ d minus 2 is less than -1 = d - 2 < - 1
Hence, the required inequality would be,
[tex]d-2 < -1[/tex]
Now, by further solving,
Add 2 on the both sides of inequality ( additive property of inequality )
[tex]d < -1 + 2\implies d < 1[/tex]
⇒ d ∈ ( -∞, 1 )
step by step what is 4 (x - 1) -3 (x + 2)
Answer:
For this expression, you will have to use the distribution property to get your answer.
First, distribute the 4 to the x and -1
[tex]4(x)=4x[/tex]
[tex]4(-1)=-4[/tex]
[tex]4x-4-3(x+2)[/tex]
Now do the same with the -3, x and 2
[tex]-3(x)=-3x[/tex]
[tex]-3(2)=-6[/tex]
[tex]4x-4-3x-6[/tex]
Now combine like terms to get your final answer
[tex]4x-3x=x[/tex]
[tex]-4-6=-10[/tex]
Thus, your solution is: x - 10
Step one: 4(x-1)-3(x+2)=0 (set equal to zero)
Step two: 4x-4-3x-6=0 (multiply numbers on the outside to inside of "( )")
Step three: x-10=0 (combine like terms)
Step four: 0+10=10, x=10 (inverse operation)
Answer: x=10
I need help with 23 please!!!
Answer:
28 questions
Step-by-step explanation:
In the first 10 mins she answered 2/5 of 40 which is 16. The remaining amount is 24 questions and half of that is 12. So she answered 12 questions in 15 mins. Finally you add them to get 28 questions in 25 minutes.
*WILL GET BRAINLIEST ANSWER* !
-4 = x/9 - 8
-x/9 = 4 - 8
-x/9 = -4
x = 4 * 9
x = 36
Which is a true statement comparing the graphs of x^2/3^2 - y^2/4^2= 1 and y^2/3^2 - x^2/4^2 = 1?
The foci of both graphs are the same points.
The lengths of both transverse axes are the same.
The directrices of = 1 are horizontal while the directrices of = 1 are vertical.
The vertices of = 1 are on the y-axis while the vertices of = 1 are on the x-axis.
Answer: B) The lengths of both transverse axes are the same.
Step-by-step explanation: Given Hyperbola equations :
[tex]\frac{x^2}{3^2}-\frac{y^2}{4^2}=1[/tex] and
[tex]\frac{y^2}{3^2}-\frac{x^2}{4^2}=1[/tex]
First one : [tex]\frac{x^2}{3^2}-\frac{y^2}{4^2}=1[/tex] is a Horizontal Hyperbola.
a = 3 and 2a = 6.
Length of transverse axis = 6.
And second one : [tex]\frac{y^2}{3^2}-\frac{x^2}{4^2}=1[/tex] is a Vertical Hyperbola.
b=3 and 2b = 6
Length of transverse axis = 6.
The lengths of both transverse axes are the same.
Therefore, correct option is B option :
The lengths of both transverse axes are the same.Answer:
B
Step-by-step explanation:
For inequalities. Greater Than, >, and Less Than, <, mean the solution does NOT contain the number. So would you use and open circle or a closed circle to graph on a number line ___________________ For inequalities. Greater Than or Equal TO, >, and Less Than or Equal TO, <, mean the solution does contain the number. So would you use and open circle or a closed circle to graph on a number line?____________________
Alicia bought 4 T-shirts for $23.00. Using the unit rate, how much would 6 T-shirts cost?
i think that you would just take 23/4=$5.75
so take 6 times 5.75 and you should get $34.5
To answer this question, we first need to determine the unit cost (cost per t-shirt).
Step 1: Find the unit cost
Alicia bought 4 T-shirts for a total of $23.00. To calculate the cost per T-shirt (the unit rate), we need to divide the total cost by the number of T-shirts.
So, $23.00 (total cost) divided by 4 (number of T-shirts) equals $5.75. Thus, the unit cost of one T-shirt is $5.75.
Step 2: Calculate the cost for 6 T-shirts
Now that we know the unit cost, we can find out how much 6 T-shirts will cost. To do this, we multiply the unit cost by the number of T-shirts.
So, $5.75 (cost per T-shirt) times 6 (number of T-shirts) equals $34.50.
Therefore, it would cost $34.50 for 6 T-shirts, given the unit rate.
I need help!
Simplifying radical expressions
1)
[tex] \sqrt[3]{135} [/tex]
2)
[tex] - 5 {}^{3} \sqrt{40} [/tex]
3)
[tex] {2}^{3} \sqrt{5} \times {4}^{3} \sqrt{8} [/tex]
Here is the solution...
1) [tex]\sqrt[3]{135} \\[/tex]
Solution
We can rewrite [tex]\sqrt[3]{135} = \sqrt[3]{27} *\sqrt[3]{5}[/tex]
Here, [tex]\sqrt[3]{27} = 3[/tex]
Now substitute the value, we get
[tex]\sqrt[3]{135} = 3 \sqrt[3]{5}[/tex]
The answer is [tex]3\sqrt[3]{5}[/tex]
2) [tex]-5\sqrt[3]{40}
Solution
[tex]-5\sqrt[3]{40} = -5\sqrt[3]{8} *\sqrt[3]{5}[/tex]
Here [tex]\sqrt[3]{8} = \sqrt[3]{2^{3} } = 2\\[/tex]
Therefore, we get [tex]-5*2\sqrt[3]{5} = -10 \sqrt[3]{5}[/tex]
The answer is-10 \sqrt[3]{5}[/tex]
2) [tex]2\sqrt[3]{5} * 4\sqrt[3]{8}[/tex]
Solution
[tex]\sqrt[3]{8} = 2[/tex]
Now plug in the above in the given expression, we get
[tex]2\sqrt[3]{5} * 4*2 = 16\sqrt[3]{5}[/tex] {2*4*2 = 16]
The answer is [tex]16\sqrt[3]{5}[/tex]
m∠1=45° and m∠3=65°
What is m∠4?
2. In right △ABC with right angle B, m∠A=(3x−8)° and m∠C=(x−2)°.
What is m∠A?
47°
67°
25°
92
The measure of angle ∣4 is 250 degrees. The measure of angle ∣A is 67 degrees.
Explanation:To find the measure of angle ∣4, we can use the fact that angles around a point add up to 360 degrees.
We know that ∣1 is 45 degrees and ∣3 is 65 degrees.
To find ∣4, we can subtract the sum of angles ∣1 and ∣3 from 360 degrees.
Therefore, ∣4 = 360 - (∣1 + ∣3) = 360 - (45 + 65) = 360 - 110 = 250 degrees.
To find the measure of angle ∣A, we can use the fact that the sum of the angles in a triangle is 180 degrees.
We know that ∣B is 90 degrees because it is a right angle.
Therefore, ∣A + ∣B + ∣C = 180 degrees.
Substituting the given values, we get (3x - 8) + 90 + (x - 2) = 180. Simplifying the equation, we get 4x + 80 = 180.
Solving for x, we get x = 25.
Substituting x back into the equation for ∣A, we get ∣A = (3(25) - 8) = 67 degrees.
What is the prime factorization of 150?
the prime factors for 150 are:
2 x 3 x 5 x 5
In exponential form:
2^1 x 3^1 x 5^2
Hope this helps
Answer:
Step-by-step explanation:the prime factors for 150 are:
2 x 3 x 5 x 5
i have 500 pennies. If I spend 6 pennies a day until i can no longer do so, at the end of one of these days i will have exactly how many pennies left?
A) 6
B)8
C)10
D)12
A) is 164 because 6 times 6 is 36. 500 - 36 is 164
What expression is equivalent to 18 1/5 - (-22 2/5) - (-40 1/5)
A plane traveled 1176 miles to Phoenix and back. The trip there was with the wind. It took 14 hours. The trip back was into the wind. The trip back took 28 hours. What is the speed of the plane in still air? What is the speed of the wind?
The plane travels at 60 mph and the wind is blowing at 20 mph.
By setting up and solving a system of equations, we find that the speed of the plane in still air is 63 mph and the speed of the wind is 21 mph.
Explanation:To answer this question, you first need to set up equations to represent the speed of the plane and the speed of the wind. You can denote the speed of the plane in still air as 'p' and the speed of the wind as 'w'. The plane's speed with the wind (going to Phoenix) is represented by p+w and against the wind (coming back) is p-w.
For the trip to Phoenix, you know that distance = speed * time. That gives us the equation 1176 = 14(p+w). After simplification, we obtain the equation, p+w = 84.
For the return flight, our equation is 1176 = 28(p-w). On simplification, we find the equation p-w = 42.
Now you have a system of equations that you can solve: p+w = 84p-w = 42. Solving these equations together, you find that the speed of the plane (p) in still air is 63 mph, and the speed of the wind (w) is 21 mph.
Learn more about Speed Calculation here:
https://brainly.com/question/19930939
#SPJ3
What is the answer
A.
B.
C.
D.
E.
option A IS correct option.
what is the approximate distance between the points (-3 -4) and (-8 1) on a coordinate grid
What does -8 1 mean do you mean -8, 1
Complete the proof showing that DE is parallel to AC
Answer: The statement is [tex]\frac{AD}{DB} +1=\frac{CE}{EB}+1[/tex] and the reason is add 1 both sides.
Explanation:
The given equation is [tex]\frac{AD}{DB} =\frac{CE}{EB}[/tex].
We know that according to the addition property the equation x=y and x+c=y+c are equivalent equations, where c is a constant.
So we can add 1 both sides in the given equation.
[tex]\frac{AD}{DB} +1=\frac{CE}{EB}+1[/tex]
Now we can take LCM and we get,
[tex]\frac{AD+DB}{DB} =\frac{CE+EB}{EB}[/tex]
The above step is the third step of the given proof. By follow the given steps we can prove that DE is parallel to AC.
Therefore, the missing step is addition of 1 on both the sides of the given equation.
To prove that DE is parallel to AC, we need to show that the lines DE and AC have the same slope. By rearranging the given equations to isolate the currents I₁, I₂, and I₃, and then setting these expressions equal to each other, we can determine the relationship between the currents and thereby the slopes of DE and AC.
Explanation:To prove that DE is parallel to AC, we need to show that the lines DE and AC have the same slope. The given equations 1₁ - 12 - 13 = 0, I₁ R₁ + I₂ R₂ = V₁, and I₂ R₂ − I₃ (R₃ + R₄) = V₂ can be rearranged to isolate the currents I₁, I₂, and I₃ in terms of voltage and resistance. By setting these expressions equal to each other, we can determine the relationship between the currents and thereby the slopes of DE and AC.
Learn more about Lines and Slopes here:https://brainly.com/question/14511992
#SPJ3
a student found the product of 8 x 10 to the 6 power + 5 x 10 to the 9th power to be 4 x 10 to 15 power what is the error
8*10^6+5*10^9 should be
5,008,000,000
Answer:
The error student make is he multiply the terms instead of addition.
Step-by-step explanation:
Given : A student found the product of 8 × 10 to the 6 power + 5 × 10 to the 9th power to be 4 × 10 to 15 power.
To find : What is the error ?
Solution :
8 × 10 to the 6 power - [tex]8\times 10^6[/tex]
5 × 10 to the 9th power - [tex]5\times 10^9[/tex]
4 × 10 to 15 power - [tex]4\times 10^{15}[/tex]
According to student, [tex]8\times 10^6+5\times 10^9=4\times 10^{15}[/tex]
We solve the expression,
[tex]=8\times 10^6+5\times 10^9[/tex]
[tex]=8\times 10^6+5000\times 10^6[/tex]
[tex]=10^6(8+5000)[/tex]
[tex]=5008\times 10^6[/tex]
The error student make is he multiply the terms instead of addition.
Twelve less than the quotient of a number and 7 is -2
(x/7)-12=-2
Add 12 to both sides.
x/7=10
Multiply both sides by 7.
x=70
Final answer: 70
hope this helps :)
estimate the product by rounding 5 times 5,503
27,515 is the actual answer.
Estimated, it is about 27,500
Hope I helped!
How many pints are in 3 gallons?
3 gallons = 24 pints
Hope this helps you!
Always remember you are a Work Of Art!
-Nicole :) <3
The figure below shows rectangle ABCD:
The following two-column proof with missing statement proves that the diagonals of the rectangle bisect each other:
Which statement can be used to fill in the blank space?
(A) ∠ABD ≅ ∠DBC
(B) ∠CAD ≅ ∠ACB
(C) ∠BDA ≅ ∠BDC
(D) ∠CAB ≅ ∠ACB
B would be the answer because if you were to search up a picture of alternate interior angles, it would be the same as <CAD and <ACB
Answer:
(B) ∠CAD≅∠ACB
Step-by-step explanation:
Given in the question quadrilateral ABCD is a rectangle and a table of two-column proof with missing statement for proves that the diagonals of the rectangle bisect each other.
If we want to prove that the diagonals bisects to each other, then for this first we will prove that ΔADE≅ΔCBE. But given in the two-column proof
∠ADB≅∠CBE , side BC= side AD . ∠CAD ≅ACD must be necessary for to prove that ΔADE≅ΔCBE (ASA postulate). Hence statement ∠CAD ≅ACD can be used to fill in the blank space.
17.
Graph the function f(g)=|g−2|+5 . What is the range of this function?
A g≥5
B g≥2
C g≤5
D g≥−5
The correct answer is A) g≥5
This is because when you look at an absolute value function, the constant at the end is the y value of the vertex. Since it is an absolute value equation, we know that the values can only go up. Therefore, it must be greater than or equal to the constant at the end (5)
True or False: The following relation is a function. {(−5,−7),(0,4),(−5,3),(9,4)}
the answer is that it is false
Antoni has read 147 pages of a book.He has completed 70% of the book.How many more pages does he need to read to finish the book
If f(x) varies directly with x and f(x)=40 when x=8, find the value of f(x) when x=2.
A. 2
B. 5
C. 10
D. 15
f(x)=40
x=8
so if x=2 it would be 40/8 which is 5
C
since the quantities vary directly then
x = kf(x) ( where k is the constant of variation )
to find k use the given condition , f(x) = 40 when x = 2
k = [tex]\frac{x}{f(x)}[/tex] = [tex]\frac{8}{40}[/tex] = [tex]\frac{1}{5}[/tex]
thus x = [tex]\frac{1}{5}[/tex]f(x)
when x = 2
f(x) = [tex]\frac{x}{k}[/tex] = [tex]\frac{2}{\frac{1}{5} }[/tex] = 10